PREPARATION OF FUTURE ENGINEER AND PEDAGOGUES TO USE COMMUNICATION TECHNOLOGIES IN VOCATIONAL EDUCATION INSTITUTIONS - Volkova Natallia Val (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология, 2019)
The present publication attempts to substantiate the peculiarities of the preparation of future engineer and pedagogues for the use of communicative technologies in the terms of the vocational education institution. The results of the survey on the degree of self-education and the level of communicative culture among engineer and pedagogues and masters of industrial training in the system of vocational education are collected and analyzed. It is concluded the engineer and pedagogues, in accordance with the acquired knowledge of the essence of communicative learning technologies, should be prepared to solve complex and innovative problems within of vocational education institutions. The structural components of the communicative culture of the future engineer and pedagogue are presented, a namely: humanistic orientation, knowledge of the fundamentals of the theory of pedagogical communication, communicative and creative abilities, the character and effectiveness of professional communication. It is found out that the abilities of engineer and pedagogue to the purposeful planning of educational work, to rational combination of different forms of work, to the appropriate selection and provision of a comprehensive educational impact on the pupil’s personality, the establishment in the vocational institution an atmosphere of creative pedagogical activity contribute the formation of the future worker of one or the other professionally significant features. It is noted it is the complex of educational influences that can activate, make the process of formation and development communicative culture of an engineer and pedagogue a bright, effective and indicative. The methods of organization classroom and extracurricular work of puples in vocational education institutions are presented and classified. Several groups of these methods are expedient for use by a qualified engineer and pedagogue. These include research methods and ones of pedagogical diagnosis; methods of goal setting and planning; methods of persuasion and formation of consciousness of the person; methods of organization of pupils’ life activity and formation of professional behavior experience; methods of motivation and stimulation; control and evaluation ones. It is concluded the main professional qualities of the personality of the engineer and pedagogue. They must have professional knowledge, spiritual and communicative culture, emotional sensitiveness, pedagogical tact, empathy, good organization, enthusiasm, ability to arrange and interest their pupils. The feature of his/her behavior, his/her emotional state, the ability to assess pedagogical situations, to find a positive emotional form of relationships, to choose the words and means to influence the pupil are essentially characterizes the communicative culture of the engineer and pedagogue. The technological methods of forming a communicative culture of an engineer and pedagogue are shown; they could be realized while implementing various forms and techniques of organizing classroom and extracurricular work, during solving and simulating communication tasks and situations, elaborating methods for managing their own mood, state of health and behavior.